Rapid green manufacture of high yield CdTe@Ca(OH)2 nanocrystals and their performance on WLED. Issue 2 (25th December 2015) - Zhao, Zhixing; Wang, Xiao‐Qiao; Ling, Luting; Wang, Cai‐Feng; Chen, Su
Abstract : The bottleneck of large‐scale production of semiconductor quantum dots (QDs) is how to solve heavy metal ions waste water and the rapid separation during industrial process. A facile strategy for fabricating CdTe@Ca(OH)2 nanocrystals exhibiting both improved photoluminescence (PL) stability and prolonged PL lifetime via an economical coprecipitating technology is reported herein. The procedure on capping CdTe QDs into Ca(OH)2 crystals can enable the products to be easily filtrating separation and the content of residual Cd 2+ filtrate solution to be reached to 0.238 ppm level. Also, fluorescent rod‐like heterocrystals by addition of saturated CaCl2 solution is constructed. CdTe@Ca(OH)2 nanocrystals is utilized further as phosphor powders to construct white light emitting diode (WLED). The WLED presented, here, has good photoelectric properties with color rendering index of 82.4 at 350 mA, a color temperature of 4643 k, and Commission Internationale de L'Eclairage coordinate of (0.3548, 0.3532), belonging to the white gamut, showing great potential in industrial application. © 2015 American Institute of Chemical Engineers AIChE J, 62: 580–588, 2016